A Nonhomothetic Generalized Leontief Cost Function Based on Pooled Data - Nakamura, Shinichiro (The Review of Economics and Statistics, 1990)
Factor demand studies of Komiya, Ozaki, Lau and Tamura based upon detailed cross-section data on individual production units have found that the nonhomothetic factor limitational ( NHT-FL) demand system, a nonhomothetic version of the Leontief fixed coefficient model, well explains the data. These results, however, have mostly been ignored in the current literature on flexible functional forms, and in fact none of the well-known nonhomothetic flexible cost function forms includes the NHT-FL model. I introduce a new nonhomothetic form of the Generalized Leontief (GL) cost function, which includes the NHT-FL model as a special case. Empirical application to a pooled data set of the Japanese iron & steel industry indicates that his form is superior to the translog, Diewert-Wales GL, and Berndt-Khaled GL forms. Copyright 1990 by MIT Press.